Parachaetocladius lenferringtoni (Diptera: Chironomidae), a new orthoclad from North America, with keys to adult males and pupae of the Nearctic Parachaetocladius (Wülker, 1959) - Jr., R. William Bouchard; Namayandeh, Armin; Hudson, Patrick L. (Zootaxa, 2024)
In this study, we describe Parachaetocladius lenferringtoni sp. nov., based on all its life stages, and provide keys to adult males and pupae of the Nearctic Parachaetocladius. The new species was originally placed in Parachaetocladius abnobaeus (Wülker 1959) due to the similarity in the hypopygium of these species. However, a detailed examination of adults and associated immature specimens demonstrates that P. lenferringtoni sp. nov. represents a single species that is different from P. abnobaeus. Diagnostic adult and pupal characters were identified to separate this new species from P. abnobaeus and other species of Parachaetocladius. The separation of the larva of P. lenferringtoni sp. nov. and P. abnobaeus is currently tenuous, but some possible diagnostic characters are provided. Material of P. lenferringtoni sp. nov. was obtained for this study from Canada (Manitoba) and the United States of America (Kansas, Minnesota, Nebraska, and Wisconsin), indicating this species is largely limited to central North America. The habitat of this new species matches that of other Parachaetocladius species in that it has been collected from sandy substrates in springs and groundwater-dominated streams.